2022
DOI: 10.3390/nano12101643
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Dipeptide Homologue-Based Hydrogels for Photocontrolled Drug Release

Abstract: Peptide-based hydrogels are considered of special importance due to their biocompatibility and biodegradability. They have a wide range of applications in the biomedical field, such as drug delivery, tissue engineering, wound healing, cell culture media, and biosensing. Nevertheless, peptide-based hydrogels composed of natural α-amino acids are limited for in vivo applications because of the possible degradation by proteolytic enzymes. To circumvent this issue, the incorporation of extra methylene groups withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Therefore, CBNs, such as graphene oxide (GO), CNTs and graphene quantum dots (GQDs) have been extensively studied in biomedical applications [ 251 , 252 ]. Guilbaud et al (2022) studied hydrogels based on short homopeptides (Boc-α-diphenylalanine and Boc-α-dityrosine) containing light-responsive nanomaterials (CNTs and GO), which offered interesting results for the development of promising systems for controlled on-demand drug release applications [ 253 ]. Park et al (2022) investigated the design and manufacture of three types of hybrid poly(NIPAAm-co-BBVIm) (pNIBBIm) and CTS hydrogels with incorporated CNTs for smart drug delivery systems, with remarkable thermal and electrical responsive properties that enabled the development of an excellent controllable and switchable drug delivery platform for biomedical approaches [ 254 ].…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…Therefore, CBNs, such as graphene oxide (GO), CNTs and graphene quantum dots (GQDs) have been extensively studied in biomedical applications [ 251 , 252 ]. Guilbaud et al (2022) studied hydrogels based on short homopeptides (Boc-α-diphenylalanine and Boc-α-dityrosine) containing light-responsive nanomaterials (CNTs and GO), which offered interesting results for the development of promising systems for controlled on-demand drug release applications [ 253 ]. Park et al (2022) investigated the design and manufacture of three types of hybrid poly(NIPAAm-co-BBVIm) (pNIBBIm) and CTS hydrogels with incorporated CNTs for smart drug delivery systems, with remarkable thermal and electrical responsive properties that enabled the development of an excellent controllable and switchable drug delivery platform for biomedical approaches [ 254 ].…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…Yet, few works report the use of peptide-based hydrogels together with liposomes as a means to compartmentalize drugs and achieve better control over the drug delivery system, 1,3 as well as the use of NIR to stimulate drug release. 55,56 In a previous work, our group demonstrated that photothermia could be used to enhance curcumin drug release from peptide-based hydrogels, 43 but this simple drug-hydrogel combination is limited to stable or well encapsulated drugs, or thermally-responsive hydrogels. If a hydrophilic molecule is loaded in a gel, its release is strongly driven by passive release and the control over it becomes limited to few choices, such as changing the hydrogel network density, as reported in the present work, in which photothermia did not enhance CF release in hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, few works report the use of peptide-based hydrogels together with liposomes as a means to compartmentalize drugs and achieve better control over the drug delivery system, 1,3 as well as the use of NIR to stimulate drug release. 55,56…”
Section: Discussionmentioning
confidence: 99%
“…This process was applied to the on-demand release of ascorbic acid. Interestingly, the same structures containing tyrosine instead of phenylalanine failed to produce hydrogels, indicating a detrimental influence of the phenol OH group on the self-assembly process [ 59 ].…”
Section: ‘Smart’ Peptide Hydrogels: Triggers For Self-assembly and Dr...mentioning
confidence: 99%